THE ORIGIN OF THE WORD “MOTHER” - Khayitova Shohida Erkin Kizi (Web of Journals Publishing, 2024)
This article presents the origin of the mother lexeme and its expression in other languages. In the framework of related and non-related languages, the comparative and comparative plan is covered with factual examples.
Keywords: lexemes mother, modor, ona, mum, “mommy, family group.